Comparative interrogation of the developing xylem transcriptomes of two wood‐forming species: Populus trichocarpa and Eucalyptus grandis. Issue 4 (6th February 2015) - Hefer, Charles A.; Mizrachi, Eshchar; Myburg, Alexander A.; Douglas, Carl J.; Mansfield, Shawn D.
Summary Wood formation is a complex developmental process governed by genetic and environmental stimuli. Populus and Eucalyptus are fast‐growing, high‐yielding tree genera that represent ecologically and economically important species suitable for generating significant lignocellulosic biomass. Comparative analysis of the developing xylem and leaf transcriptomes of Populus trichocarpa and Eucalyptus grandis together with phylogenetic analyses identified clusters of homologous genes preferentially expressed during xylem formation in both species. A conserved set of 336 single gene pairs showed highly similar xylem preferential expression patterns, as well as evidence of high functional constraint. Individual members of multi‐gene orthologous clusters known to be involved in secondary cell wall biosynthesis also showed conserved xylem expression profiles. However, species‐specific expression as well as opposite (xylem versus leaf) expression patterns observed for a subset of genes suggest subtle differences in the transcriptional regulation important for xylem development in each species. Using sequence similarity and gene expression status, we identified functional homologs likely to be involved in xylem developmental and biosynthetic processes in Populus and Eucalyptus. Our study suggests that, while genes involved in secondary cell wall biosynthesis show high levels of gene expression conservation, differential regulation of some xylem development genes may give rise to unique xylem properties.